Inoculum Concentration and Mineral Fertilization: Effects on the Endophytic Microbiome of Soybean - dos Santos, Roberta Mendes; Cueva-Yesquén, Luis Gabriel; Garboggini, Fabiana Fantinatti; Desoignies, Nicolas; Rigobelo, Everlon Cid (Frontiers in Microbiology, 2022)
Soybean crops are of great economic importance worldwide and in Brazil. This crop is a commodity that provides large amounts of financial resources to the country. Soybean productivity is influenced by several biotic and abiotic factors, and most of these factors cannot be controlled by agricultural practices. Due to the soybean cultivars used and their required yields, the soybean crop, similar to other agriculturally important crops, requires large amounts of mineral fertilizers. There are several microorganisms that colonize soybean plant roots without causing symptoms or damage. These microorganisms that colonize plant tissues are called endophytes and can often promote plant growth and development. Little is known about the factors that influence endophyticism. The aim of the present study was to evaluate whether B. subtilis inoculant concentrations and levels of mineral fertilization recommended for the crop have any influence on the endophytic microbiome of soybean plant roots. The results show that B. subtilis inoculations did not affect the endophytic community of the roots; however, the evaluation of the microbial community structure according to the alpha diversity metrics observed richness, Chao1 index, Shannon index and Simpson index showed that microbial diversity of endophytes was higher at fertilization levels of 50 and 100%, with a significant difference (p<0.05) between 0 and 50% and 0 and 100% fertilization.